Factors Influencing Organizational Commitment - Marhaposan Situmorang, Roni; B, Mesra (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This study aims to look at the Effect of Intellectual Intelligence on Organizational Commitment with Work Culture as an Intervening Variable at Bpjs Kota Kisaran Branch and Padang Sidempuan Branch. This type of research uses quantitative methods, this research was conducted at the BPJS Employment Branch Office of Kisaran City and Padang Sidempuan Branch, the population used was 80 employees consisting of 42 personnel from the Kisaran city branch, 38 personnel from the Padang Sidempuan branch. The sample used is all the population of 80 employees with saturated samples being the sample technique. The data source used is primary data source and data collection by distributing questionnaires. This research model uses analysis and the measuring instrument is the smart PLS version 3.3.3 application. The results of this study are as follows Intellectual Intelligence has a positive and significant effect on work culture with an original sample value of 0.685 and p values of 0.000. Work Culture has a positive and significant effect on organizational commitment with an original sample value of 0.214 and P values of 0.000. Intellectual Intelligence has a positive and significant effect on organizational commitment with an original sample value of 0.684 and p values of 0.000.